REAKSI PASAR ATAS PENGUMUMAN CORPORATE GOVERNANCE PERCEPTION INDEX - Dwi Utami, Ni Made Sasmita; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
Corporate Governance Perception Index (CGPI) is the result of research of The Indonesian Institute for Corporate Governance (IICG) in cooperation with SWA magazine as a media publication. The goal is to create an index ranking of the best of each companies that has implemented the concept of good corporate governance and the only one in Indonesia. This study aims to determine the market reaction to the announcement CGPI shown with abnormal return and trading volume activity. This study population is a company that surveyed CGPI during 2010-2014. Sampling techniques using non-probability sampling is purposive sampling and selected 95 samples. Hypothesis testing is done is one-sample t-test and Two ways analysis of variance (ANOVA). These results indicate that the announcement CGPI reacted by market demonstrated significant trading volume activity. Additionally, testing showed no difference in abnormal return and trading volume activity significantly in each predicate in each window period.
Keywords: Announcement of Corporate Governance Perception Index, Abnormal Return, Trading Volume Activity